The "dark ages" of German macroeconomics and other alleged shortfalls in German economic thought - Lars P. Feld; Ekkehard A. Köhler; Daniel Nientiedt (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2017)
Ordoliberalism is often accused as being responsible for Germany's policy stance during the Eurozone crisis. Ordoliberalism originates from the so-called Freiburg School of Economics, founded by Walter Eucken during the 1930s at the University of Freiburg, which is in fact in Germany. It is however neither true that ordoliberal thought has continuously been predominant and a prevailing idea in German macroeconomic policy, nor that it is responsible for Germany's policy stance during the crisis in EMU. In this paper, we show why a proper analysis must arrive at this conclusion by referring to Eucken's thinking and the development of German ordoliberalism across time in relation to the "Rules vs. Discretion" debate and to Constitutional Economics. Although ordoliberalism may have had some influence on the design of EMU, pragmatism, the status-quo and national interests are dominant in German economic policy.
Keywords: B13; B26; B31; D78; E61; E63; 330; Ordoliberalism; Eurozone Crisis; Constitutional Economics; Monetary and Fiscal Policy